2018
DOI: 10.1038/s41598-018-33859-0
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution isotopic evidence for a potential Saharan provenance of Greenland glacial dust

Abstract: Dust concentrations in Greenland ice show pronounced glacial/interglacial variations with almost two orders of magnitude increase during the Last Glacial Maximum. Greenland glacial dust was previously sourced to two East Asian deserts: the Taklimakan and Gobi deserts. Here we report the first high-resolution Pb and Sr isotopic evidence for a significant Saharan dust influence in Greenland during the last glacial period, back to ~31 kyr ago, from the Greenland NEEM ice core. We find that during Greenland Stadia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 46 publications
3
39
0
Order By: Relevance
“…Lupker et al (2010) analysed the Sr and Nd isotopic ratios of mineral dust in an ice core from southern Greenland (Dye 3) in the age range of 1786-1793 CE and revealed that the Sahara might be an additional dust source. Han et al (2018) showed temporal variations in the source areas of the NEEM ice core dust based on Sr and Pb isotope analysis; the primary dust source was eastern Asian deserts from 31 to 23 kyr and the Sahara from 23 to 12 kyr. However, these analyses have targeted mostly ice core dust from glacial periods characterized by a high dust concentration because Sr and Nd isotopic ratio analyses need large numbers of samples.…”
mentioning
confidence: 99%
“…Lupker et al (2010) analysed the Sr and Nd isotopic ratios of mineral dust in an ice core from southern Greenland (Dye 3) in the age range of 1786-1793 CE and revealed that the Sahara might be an additional dust source. Han et al (2018) showed temporal variations in the source areas of the NEEM ice core dust based on Sr and Pb isotope analysis; the primary dust source was eastern Asian deserts from 31 to 23 kyr and the Sahara from 23 to 12 kyr. However, these analyses have targeted mostly ice core dust from glacial periods characterized by a high dust concentration because Sr and Nd isotopic ratio analyses need large numbers of samples.…”
mentioning
confidence: 99%
“…S1). During GS 5.1 (HS 3) dust mainly sourced from central Asian deserts 11 , suggesting, as the main drivers of the observed dust increase, the pronounced continental aridity and increased soil dust availability coupled with more efficient atmospheric transport and reduced en route dust removal. Such reorganizations seem to have happened in close association to the millennial and-sub-millennial scale ITCZ-monsoon system variability [25][26][27] , as documented in lowlatitudes high-resolution marine and terrestrial records.…”
Section: Linking Hs 3 Mid-latitude Ecosystem Variability To Changes Imentioning
confidence: 99%
“…These isotope ratios do not fractionate during industrial processes, making them a promising tool for identifying pollution sources 28 , 29 . This technique has been deployed to study PM sources in the atmosphere 14 , 18 , 30 33 as well as the sources of particles in ice cores 29 , 34 , 35 .…”
Section: Introductionmentioning
confidence: 99%